DNA Sequencing from Subcritical Concentration of Cell-Free DNA Extracted from Electrowetting-on-Dielectric Platform - Alias, Anand Baby; Huang, Hong-Yuan; Wang, Yi-Wen; Lin, Kai-Ti; Lu, Pei-Jhen; Wu, Tzu-Hui; Jiang, Pei-Shin; Chen, Chien-An; Yao, Da-Jeng (Micromachines (Basel), 2022)
Electro-Wetting-On-Dielectric (EWOD) based digital operations have demonstrated outstanding potential in actuating and manipulating liquid droplets. Here, we adapted the EWOD for extracting femtogram quantities of cell-free DNA (cf-DNA) from 1 μL of KSOM mouse embryo culture medium. Our group extracted the femtogram quantity of cf-DNA from 1 μL of mouse embryo culture medium in our previous work. Here, we initially explain a modification from our previous extraction protocol, which improves the extraction percentage to 36.74%. Though the modified extraction protocol improves the extraction percentage from our previously reported work, the quantity is still in the femtogram range. The cf-DNA in femtogram quantity is in subcritical/subthreshold concentration for any further analysis, such as sequencing. To the best of our knowledge, we need a minimum of picogram/nanogram DNA quantities for further analysis. We demonstrated a ground-breaking mechanism of this subcritical concentration of cf-DNA amplification to the nanogram range and performed DNA sequencing. Basic Local Alignment Search Tool (BLAST) is used as a sequence similarity search program to confirm the identity percentage between query and subject. More than 97% of nucleotide identities between query and subject sequences have been obtained from the sequencing result. Hence, we can use the methodology to amplify the subcritical concentration of extracted DNA for further analytics. Moreover, as we extract the cf-DNA from the embryo culture medium, the natural growth of the embryo has not been disrupted. This entire mechanism will pave a new path towards the lab-on-a-chip (LOC) concept.